Измерение ценности в проектах комплексного развития территорий - Коростелев, Юрий Сергеевич (Недвижимость: экономика, управление, 2025)
В статье рассматривается проблема разграничения и учета понятий стоимости и ценности при реализации проектов комплексного развития территорий (КРТ). Анализируется традиционный фокус на экономической стоимости и обосновывается необходимость расширения оценки за счет включения многогранной ценности, охватывающей социальные, экологические, культурные и эстетические аспекты. Особое внимание уделяется роли государственного оператора КРТ как потенциального представителя долгосрочных ценностей и интересов будущих поколений. Предлагаются подходы к оценке и интеграции различных аспектов ценности с использованием квалиметрического анализа и генеративных нейронных сетей в процессы принятия решений в рамках КРТ. The article discusses the important problem of distinguishing and taking into account the concepts of cost and value in the process of implementing integrated territorial development (ITD) projects. The traditional approach to evaluating such projects often focuses solely on the economic cost, which can lead to ignoring other equally significant aspects that affect the quality of the urban environment. This paper substantiates the need to expand the assessment, including the multifaceted aspects of value, encompassing social, environmental, cultural and aesthetic factors. Special attention is paid to the role of the state-owned ITD operator as a potential representative of the long-term interests and values of future generations. New approaches to the assessment and integration of various aspects of value using qualimetric analysis and generative neural networks are proposed. These methods can be implemented in decision-making processes, which will take into account the interests of all stakeholders and create a more sustainable and comfortable urban environment. Thus, this study highlights the importance of an integrated approach to the evaluation of ITD projects.